Identification of Variables Affecting the Number of Traffic Accident Casualties (Intersections (4 and T) in Yogyakarta) - Dewi, Ari Tri Kusuma; Siregar, Martha Leni; Soehodho, Sutanto (Transpublika Publisher, 2025)
Yogyakarta has recorded a relatively high rate of traffic accidents, with a consistent trend throughout 2024. This condition is influenced by high traffic density, a consequence of increased activity in the education, tourism, and economic sectors, despite the implementation of various mitigation efforts. The aim of this study is to identify the variables that potentially influence the number of traffic accident casualties at (4 and T) intersections in Yogyakarta. The study utilized initial data collection through CCTV recordings at accident locations, data from the Integrated Road Safety Management System (IRSMS), Google Street View observations, and multiple linear regression analysis combined with variable reduction based on Variance Inflation Factor (VIF) values. The results indicate that eight variables significantly influence the number of traffic accident casualties in Yogyakarta. However, limited Smart City CCTV coverage restricts comprehensive analysis. Future research requires expanded intersection monitoring and extended study scope to enhance validity and representation.